2021
DOI: 10.3390/genes12040598
|View full text |Cite
|
Sign up to set email alerts
|

piRNA-823 Is a Unique Potential Diagnostic Non-Invasive Biomarker in Colorectal Cancer Patients

Abstract: Early detection of colorectal cancer (CRC) is the most important factor in deciding its prognosis, so the need to develop an accurate screening test is a must. P-element induced wimpy testis (PIWI) RNA-823 (piR-823) is one of the first piRNAs recognized to be linked to malignancy. We aimed to investigate the expression levels of piR-823 in both serum and tissues of colorectal cancer patients and the ability to use its serum level as a non-invasive diagnostic biomarker to detect colorectal cancer. We determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…In breast cancer, the levels of piR-4987 are positively correlated with lymph node metastasis (Huang et al, 2013). In addition, piR-823 expression is 2-fold higher in poorly differentiated colorectal cancer (CRC) tissues than in well/moderately-differentiated CRC tissues (Sabbah et al, 2021). The upregulation of piR-823 is associated with the presence of distant metastasis in gastric cancer (GC) patients (Cui et al, 2011).…”
Section: Piwi-interacting Rnas In Digestive System Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…In breast cancer, the levels of piR-4987 are positively correlated with lymph node metastasis (Huang et al, 2013). In addition, piR-823 expression is 2-fold higher in poorly differentiated colorectal cancer (CRC) tissues than in well/moderately-differentiated CRC tissues (Sabbah et al, 2021). The upregulation of piR-823 is associated with the presence of distant metastasis in gastric cancer (GC) patients (Cui et al, 2011).…”
Section: Piwi-interacting Rnas In Digestive System Cancersmentioning
confidence: 99%
“…By using pulldown assay or reporter assay, those molecules that interact with piRNAs (proteins or RNAs) could be determined. (Cui et al, 2011;Sabbah et al, 2021). The aberrant piRNA expression affects the tumorigenesis and progression of digestive system cancers (Figures 2, 3).…”
Section: Piwi-interacting Rnas In Digestive System Cancersmentioning
confidence: 99%
“…For instance, Sabbah et al evaluated the serum levels of piR-823 as a non-invasive diagnostic biomarker to detect CRC cases, finding that this piRNA was significantly increased in the serum of CRC patients compared to those samples from healthy donors. The ROC curve showed an AUC value of 0.933 for piR-823 (83.3% sensitivity and 89.3% specificity) [ 67 ], which reaffirms the idea that this piRNA not only could be considered a promising prognostic marker and therapeutic target for colorectal neoplasia but also could be used as a biomarker to detect this malignancy in the future.…”
Section: The Role Of Pirnas In Gastrointestinal (Gi) Cancersmentioning
confidence: 64%
“…In the case of tissue samples, the authors confirmed the overexpression of piR-823 in CRC tissues and its association with those poorly differentiated tumors. In addition, they also found that higher piR-823 levels were associated with advanced TNM stages (III–IV) [ 67 ]. Therefore, both studies suggest that piR-823 can act as a potential prognostic marker and as a promising therapeutic target for CRC [ 66 , 67 ].…”
Section: The Role Of Pirnas In Gastrointestinal (Gi) Cancersmentioning
confidence: 99%
See 1 more Smart Citation